From Locatio Operarum to Contratto D’Opera: Services Agreement in Italian Legal History - M. M. Pestov (Теоретическая и прикладная юриспруденция)
In the article are regarded three stages of services agreement formation in Italian law. Author demonstrates adaption of the Roman Law contract locatio-conductio in Middle Ages and Modern Period and steading forthcoming of differences characterizing this contract across European borders. The first stage of services agreement codification is revealed with the Italian Civil Code of 1865. In the article are explained causes of changes happened at the second stage of codification and the main features characterizing services agreement at the modern Italian Civil Code of 1942. The conducted research shows that after influence of French and German legislators Italian scholars produced universal rules for conducting any operation. At the same moment, that rules does not exclude the necessity to divide services agreement from other contracts.